Nature as Divine Hope: A Transcendental Perspective of Hope is the Thing with Feathers - Kornelia Sandra Permata; Liem Satya Limanta (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
Emily Dickinson's poem Hope is the Thing with Feathers depicts hope as a powerful presence within the human soul that endures under any circumstances. However, the poem's natural symbolism can also be used to portray hope as a spiritual energy inherent in the human spirit. The purpose of this paper is to investigate the poem's transcendental significance by looking at how natural elements serve as a medium for connecting human experience to spiritual values. This analysis draws on Buell’s conception of transcendentalist aesthetics to interpret Emily’s use of nature as a spiritual medium, employing Lawrence Buell’s Literary Transcendentalism: Style and Vision in the American Renaissance (1973) as its primary theoretical framework. In addition, the interpretation uses Christian symbolic tradition as an intertextual reference to highlight the spiritual resonance of the poem's imagery, without addressing biblical texts as sources of religious doctrine. The findings show that Emily uses nature as a type of spiritual reflection to mediate the link between humans and the divine. As a result, the bird in the poem serves as more than just a sign of hope; it can also be regarded as symbolically resonating with depictions of the Holy Spirit, who sustains hope within the human soul.